Peran Sistem Informasi Desa Dalam Peningkatan Pelayanan Publik Di Desa Pertumbukan Kecamatan Wampu - Kurniawan, Fahmi; Putra, Randi Rian; Aldi Alvin (Universitas Sari Mutiara Indonesia Medan, 2024)
This research discusses the role of village information systems in improving public services in Pertumbukan Village, Wampu District. The village information system is an important tool that can optimize various aspects of administration and services to village communities. In this research, various benefits were identified from implementing a village information system, including efficiency in data management, transparency in administration, and increased access to information for the community. Through observation and interview methods, this research found that the implementation of the village information system in Pertumbukan Village has had a significant positive impact on the quality of public services. It is hoped that the results of this research can be a reference for other villages in adopting information technology to improve services to the community.